Targeted next-generation sequencing (NGS) analysis of mutations in nonsyndromic tooth agenesis candidate genes: Analysis of a Turkish cohort - Keskin, Gül; Karaer, Kadri; Uçar Gündoğar, Zübeyde (Journal of orofacial orthopedics, 2022)
Purpose The goal of this study was to assess genes known to be associated with tooth agenesis with next-generation sequencing (NGS) and analyze the relationship between these mutations and tooth agenesis phenotypes. Methods The study included 49 individuals aged between 6 and 13 years. A total of 14 genes related to nonsyndromic tooth agenesis were selected for targeted NGS. Mutations in Msh homeobox 1 ( MSX1 ), Wnt family member 10A ( WNT10A ), axis inhibition protein 2 ( AXIN2 ), keratin 17 ( KRT17 ), lipoprotein receptor 6 ( LRP6 ), and secreted protein, acidic and rich in cysteine (SPARC)-related modular calcium-binding protein 2 ( SMOC2 ) genes were investigated. Results Mutations in six genes were detected in 12 of 49 subjects. Fifteen variants were identified, including the unknown variants c.657G > C in MSX1 , c.2029C > T in AXIN2 , and c.1603A > T in LRP6 . Second premolar tooth agenesis was observed in 43.3% of all tooth agenesis cases with mutations, and it was the predominant phenotype observed for each mutated gene, followed by tooth agenesis of the lateral incisors (20%). Conclusions Variations in MSX1, WNT10A, AXIN2, KRT17, LRP6 , and SMOC2 may be a risk factor for hypodontia or oligodontia in the Turkish population.